HUBUNGAN SIFAT FISIK TANAH TERHADAP KERUSAKAN TANAMAN CEMPEDAK PADA LAHAN REHABILITASI DAERAH ALIRAN SUNGAI (DAS) DESA TIWINGAN LAMA KABUPATEN BANJAR - Susilawati Susilawati; Yusanto Nugroho; Normela Rahmawati; Gt. Seransyah Rudy (Lambung Mangkurat University-Indonesia, 2022)
Watershed rehabilitation lands are generally critical land. Planting is done there need to be evaluation of growth and health of plants. The purpose of this research is to analyze and evaluate the growth of tolerant crops that are Cempedak (Artocarpus integer) and Durian (Durio Zibethinus) as well as analyzing the amount of health of plants and the percentage of tolerant crops in the rehabilitation Tiwingan Lama Banjar District. The research method is performed purposive random sampling with 9 plot samples of each type of plant. The plot of research used is a circular plot measuring 7.94 meters. The percentage of life of the plant is calculated from the number of plants that live at the time of research divided the total number of plants in the early planted. Collection of identification data of plant health status is done by FHM (Forest Health Monitoring) method. The percentage of life of the plant is tolerant of the Watershed rehabilitation land for the Cempedak of 68.17% and for the type of durian 62.62% which is entered into medium category. Growth of the best Cempedak plant at the age of ± 4 years in the slope 26-45% have a volume increments of 0, 0116M3/year and the growth of the best durian plants in the slope of 16-25% with a volume increments 0.0587 m3/year. The health value of the tolerant plant to 3 (three) classes of slope indicating health with a healthy classification with mild damage.